The Effect Of Profitability, Leverage, Company Size, Liquidity, And Free Cash Flow On The Dividend Payout Ratio In Hidiv20 Index Companies Listed On The Indonesia Stock Exchange - James Riady (International Journal of Economics Accounting and Management, 2025)
This study aims to analyze the effect of profitability, leverage, company size, liquidity, and free cash flow on dividend payout ratio in companies included in the HIDIV20 index on the Indonesia Stock Exchange during the period 2017–2022. The research method used is a quantitative approach. The data used are secondary data in the form of company financial reports obtained from the official website of the Indonesia Stock Exchange and the annual reports of each company. The results of the study indicate that company size has a significant negative effect on dividend distribution. This indicates that companies with larger sizes tend to pay lower dividends, possibly due to the priority of allocating funds to internal needs, such as investment or expansion. Meanwhile, other independent variables, namely profitability, leverage, liquidity, and free cash flow, do not have a significant effect on dividend distribution